The Genetic and Morphoagronomy Character Diversity of Black Soybean Plant (Glycine soja (L.)): Responses to Mutation Induction by Gamma Rays Irradiation and Ethyl Methane Sulfonate - Fauziah, Shaddiqah Munawaroh; Savitri, Evika Sandi; Arumingtyas, Estri Laras (The Journal of Experimental Life Science, 2020)
Indonesia has a high dependence on imports of black soybeans. National black soybean needs continue to increase. Therefore, some efforts are needed to increase soybean production. Genetic resources of Black Soybeans with high diversity is also needed to develop superior varieties. One of the ways to increase soybean production is by mutation induction. Therefore, genetic resources of Black Soybeans with high diversity is needed to develop superior varieties. Mutagenesis using gamma rays and EMS can be used to increase genetic diversity. Doses used in this research were 1000 Gy gamma rays, 1% EMS, and combinations. This research was using a completely randomized design with morphoargonomy and molecular parameters. Morphoagronomy parameters observed were plant height, leaf area, seed weight, number of leaves, number of pods, and number of branches. ISSR markers with four primers (UBC 888, ISSR3, UBC876, and UBC889) were used to determine genetic variation of Black Soybeans. Based on the analysis of variance (ANOVA), it was shown that all parameters were able to give an effect on the morphoagronomy of black soybean plants. Gamma rays 1000 Gy were more effective in improving morphoagronomy of the plant in terms of plant height, seed weight, number of leaves, number of pods, leaf area, and number of branches. UBC 888 was the most effective primer to identify the genetic diversity of black soybeans that have been given mutation treatments.   Keywords: Black soybean, EMS, gamma rays, genetic variation, morphoagronomy.